Reprogramming of the Caseinolytic Protease by ADEP Antibiotics: Molecular Mechanism, Cellular Consequences, Therapeutic Potential - Brötz-Oesterhelt, Heike; Vorbach, Andreas (Frontiers in Molecular Biosciences, 2021)
Rising antibiotic resistance urgently calls for the discovery and evaluation of novel antibiotic classes and unique antibiotic targets. The caseinolytic protease Clp emerged as an unprecedented target for antibiotic therapy 15 years ago when it was observed that natural product-derived acyldepsipeptide antibiotics (ADEP) dysregulated its proteolytic core ClpP towards destructive proteolysis in bacterial cells. A substantial database has accumulated since on the interaction of ADEP with ClpP, which is comprehensively compiled in this review. On the molecular level, we describe the conformational control that ADEP exerts over ClpP, the nature of the protein substrates degraded, and the emerging structure-activity-relationship of the ADEP compound class. On the physiological level, we review the multi-faceted antibacterial mechanism, species-dependent killing modes, the activity against carcinogenic cells, and the therapeutic potential of the compound class.